Iceman & Angel - Clevinger, Brian, 1978- (X-Men, first class., 2012)
"Nothing ruins spring break faster for Iceman and Angel than a giant monster stomping through the streets of their city. But what are two young mutants to do when all the 'real' superheroes are too busy to help? And why is Goom, the Thing from Planet X, running amok in the first place? It's a superhero mutant monster spring-break bash! Woo!"--P. [4] of cover.